2021
DOI: 10.1007/s00415-021-10876-0
|View full text |Cite
|
Sign up to set email alerts
|

Can intracranial time-of-flight-MR angiography predict extracranial carotid artery stenosis?

Abstract: Objectives Extracranial stenosis of the internal carotid artery (ICA) is an important cause of ischemic stroke and transient ischemic attack (TIA). It can be diagnosed using contrast-enhanced CT or MR angiography (MRA) as well as Doppler ultrasound. In this study, we assessed the diagnostic value of intracranial time-of-flight (TOF) MRA to predict extracranial ICA stenosis (ICAS). Methods We retrospectively analyzed consecutive patients with acute ischemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…[ 33 , 34 ] Many studies have shown that TOF MRA may be at least as accurate, if not more than contrast-enhanced MRA, in the assessment of stenosis and/or occlusion of intracranial and extracranial arteries in the evaluation of ischemic stroke. [ 35 , 36 ] Since we have included only TOF MRA in this study; thus, our absolute results may be limited to the assessment of intracranial stenosis by TOF MRA only; however, the principles and concept conveyed by our results may also apply to CE MRA, CT angiography, as well as DSA assessment of intracranial stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…[ 33 , 34 ] Many studies have shown that TOF MRA may be at least as accurate, if not more than contrast-enhanced MRA, in the assessment of stenosis and/or occlusion of intracranial and extracranial arteries in the evaluation of ischemic stroke. [ 35 , 36 ] Since we have included only TOF MRA in this study; thus, our absolute results may be limited to the assessment of intracranial stenosis by TOF MRA only; however, the principles and concept conveyed by our results may also apply to CE MRA, CT angiography, as well as DSA assessment of intracranial stenosis.…”
Section: Discussionmentioning
confidence: 99%